CLIMATE CHANGE AND PUBLIC HEALTH: AWARENESS, ATTITUDE, AND PRACTICES OF RURAL RESIDENTS IN NORTHERN VIETNAM (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the knowledge, attitudes, and practices (KAP) regarding climate change and its health impacts, and to analyze the correlation between attitudes and practices among rural populations in Northern Vietnam in 2025.Methods: A cross-sectional descriptive study was conducted with 446 participants using a structured questionnaire covering demographics and KAP dimensions. Descriptive statistics and correlation analyses were employed to determine the relationships between variables.Results: Findings revealed that 82.1% of participants had heard of climate change, primarily via mass media (76.3%) and social networks (39.8%). Although 80.7% acknowledged the health risks of climate change, only 54.9% could identify specific conditions such as vector-borne and non-communicable diseases. Regarding attitudes, 72.9% expressed significant concern over health impacts, and 76.9% advocated for relevant communication activities and policies. In terms of practices, the most common actions were resource conservation (73.1%) and environmental protection or waste management (67.6%). A significant positive correlation was observed between attitude and practice scores (r = 0.56; p < 0.001), indicating that higher awareness and concern drive proactive adaptation behaviors.Conclusion: While basic awareness of climate change is high, adaptive and preventive practices remain moderate. These results underscore the urgent need for enhanced community education and the integration of health-centered climate communication strategies to bolster local resilience and community engagement.
Keywords: climate change; public health; awareness; attitude; practices; rural population